2023
DOI: 10.3389/fimmu.2023.1175387
|View full text |Cite
|
Sign up to set email alerts
|

Update on transfusion-related acute lung injury: an overview of its pathogenesis and management

Abstract: Transfusion-related acute lung injury (TRALI) is a severe adverse event and a leading cause of transfusion-associated death. Its poor associated prognosis is due, in large part, to the current dearth of effective therapeutic strategies. Hence, an urgent need exists for effective management strategies for the prevention and treatment of associated lung edema. Recently, various preclinical and clinical studies have advanced the current knowledge regarding TRALI pathogenesis. In fact, the application of this know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…The results of this study found that Transfusion-related acute lung injury (TRALI) had the strongest signal strength. TRALI is a clinical syndrome with clinical features including acute dyspnea, hypoxemia, fever, hypotension, tachycardia, and leukopenia ( Yu and Lian, 2023 )]. One of the major causes of transfusion-related death is the occurrence of hypoxia-associated acute noncardiogenic pulmonary oedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study found that Transfusion-related acute lung injury (TRALI) had the strongest signal strength. TRALI is a clinical syndrome with clinical features including acute dyspnea, hypoxemia, fever, hypotension, tachycardia, and leukopenia ( Yu and Lian, 2023 )]. One of the major causes of transfusion-related death is the occurrence of hypoxia-associated acute noncardiogenic pulmonary oedema.…”
Section: Discussionmentioning
confidence: 99%
“…This can happen during or after a blood transfusion and is caused by damage to the pulmonary vasculature. Antibodies to human neutrophil antigens (HNAs) or human leukocyte antigens (HLAs) in the donor’s blood can bind to the recipient’s antigens and mediate this damage ( Yu and Lian, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate production of IL-10, a regulatory cytokine to counter-regulate interferon- γ , might be related to the development of MAS ( 24 ). Several of these cytokines (IL-6, IL-10) are also important in the pathophysiology of TRALI ( 21 ). Based on the several overlapping mechanisms involved in the pathophysiology of MAS in sJIA and those identified as triggers/risks for TRALI, our patient had significant recipient-related risk factors that could have contributed to the onset of TRALI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, monocyte and macrophage activation has also been implicated in the pathophysiology of TRALI. Several activation mechanisms of these cells have been described, such as those mediated by pathogen-associated and damage-associated molecular patterns and their receptors, antibodies, complement, as well as neutrophil extracellular traps (10,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%